DESIGN METHODS FOR COMPLIANT MECHANISMS USED IN NEW AGE INDUSTRIES – A REVIEW - Arumugam, Pandiyan; Kumar, Arun (Journal of Applied Engineering Science, 2016)
Compliant mechanisms have made an enormous contribution in various fields. Several methods have being conceived to analyze and design these compliant mechanisms that gain part of their motion from the deflection of flexible members rather than from movable joints only. Traditional rigid-body mechanisms have a number of components to apply their functions. Consequently they face problems such as backlash, wear, and increase in part-count, weight, assembly cost and time, regular maintenance. By reducing these problems will assist in increasing mechanism performance and cost reduction. Recently, many familiar examples of compliant mechanisms have been designed and widely used in various fields such as automotive industry, aerospace industry, MEMS, Medical devices, Robotic arm with minimal impedance due to its own mass & assistive mechanisms. For adaptive structures, components in transportations, hand-held tools, etc. however, the largest challenge was relative difficulty in analyzing and designing compliant mechanisms. Two approaches studied in the literature of kinematics-based approach and the structural optimization based approach. At present work is being carried out to analyze, the best suitable optimization method for designing a compliant mechanisms used in new age industries.
Keywords: Structural Optimization Approach; Kinematics-based Approach; Compliant Mechanisms